Lifetime cost of ischemic stroke in Germany: Results and National Projections From a population-based stroke registry. The Erlangen Stroke Project - Kolominsky-Rabas, Peter; Heuschmann, Peter; Marschall, Daniela; Emmert, Martin; Baltzer, Nikoline; Neundörfer, Bernhard; Schöffski, Oliver; Krobot, Karl J. (Stroke, 2006)
Background and Purpose - The number of stroke patients and the healthcare costs of strokes are expected to rise. The objective of this study was to determine the direct costs of first ischemic stroke and to estimate the expected increase in costs in Germany. Methods - An incidence-based, bottom-up, direct-cost-of-ischemic-stroke study from the third-party payer's perspective was performed, incorporating 10-year survival data and 5-year resource use data from the Erlangen Stroke Registry. Discounted lifetime year 2004 costs per case were obtained and applied to the expected age and sex evolution of the German resident population in the period 2006 to 2025. Results - The overall cost per first-year survivor of first-ever ischemic stroke was estimated to be 18 517 euros (EUR). Rehabilitation accounted for 37% of this cost, whereas in subsequent years outpatient care was the major cost driver. Discounted lifetime cost per case was 43 129 EUR overall and was higher in men (45 549 EUR) than in women (41 304 EUR). National projections for the period 2006 to 2025 showed 1.5 million and 1.9 million new cases of ischemic stroke in men and women, respectively, at a present value of 51.5 and 57.1 billion EUR, respectively. Conclusions - The number of stroke patients and the healthcare costs of strokes in Germany will rise continuously until the year 2025. Therefore, stroke prevention and reduction of stroke-related disability should be made priorities in health planning policies. © 2006 American Heart Association, Inc.
WiSo-Import:2015-03-26:4363
Keywords: Cost of illness; Costs and cost analysis; Ischemic stroke; Resource use; Stroke